2019
DOI: 10.1016/j.aott.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elastofibroma dorsi on CT: Is it really an uncommon entity?

Abstract: Objective The aim of this study was to determine the prevalence, demographic data of elastofibroma dorsi (ED) in adult population who had undergone chest CT examination and to discuss clinical, and radiological presentations, and treatment options of ED. Methods We retrospectively reviewed 4074 chest CT examinations for ED from July 2014 to April 2015. Lesion size, side, and patient demographics were analyzed for positive cases of ED. The initial radiology reports of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 15 publications
4
36
3
1
Order By: Relevance
“…It is not encapsulated, originates from fibrous tissue and has a slow growth tendency 1 . ED is not an uncommon lesion, and especially seen in females and older age groups 2 . In the autopsy series performed on a group over 55 years old, ED lesion was found in 24.4% of women 3 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is not encapsulated, originates from fibrous tissue and has a slow growth tendency 1 . ED is not an uncommon lesion, and especially seen in females and older age groups 2 . In the autopsy series performed on a group over 55 years old, ED lesion was found in 24.4% of women 3 .…”
Section: Introductionmentioning
confidence: 89%
“…1 ED is not an uncommon lesion, and especially seen in females and older age groups. 2 In the autopsy series performed on a group over 55 years old, ED lesion was found in 24.4% of women. 3 From an etiological perspective, different hypotheses have been proposed for ED.…”
Section: Introductionmentioning
confidence: 94%
“…Elastofibroma is not a true neoplastic process and may be engendered by repetitive micro-trauma or friction of the inferior pole of the scapula with the thoracic wall. Repetitive, mechanical trauma induces reactive hyper-proliferation and degeneration of fibro-elastic tissue [3,4]. Elastofibroma arises in regions of limited mechanical friction and can appear within dominant and non-dominant sides.…”
Section: Nov Appro In Can Studymentioning
confidence: 99%
“…Although previously believed to be rare, elastofibroma has a prevalence of 2.73%, as shown by a large retrospective study through computed tomography (CT) images [2]. Autopsy studies have reported an even higher prevalence of up to 24% in the elderly population [3].…”
Section: Introductionmentioning
confidence: 99%